Unraveling the impact of the new Saudi company regulations: Enhancing financial reporting quality and achieving vision 2030 - Alomair, Abdulrahman; Al Naim, Abdulaziz Saud (Asian Economic and Financial Review, 2024)
This research examines the direct and indirect effects of the New Saudi Company Regulations (NCR) on financial reporting quality (FRQ) in the Saudi stock market (Tadawul) from 2015–2017. The final sample comprises 60 companies (180 observations). Such institutional changes are expected to impact FRQ in Saudi Arabia. Thus, this research aims to theoretically and empirically investigate how Saudi company-specific characteristics influence FRQ given the changing institutional environment. The study reviewed the NCR changes against prior study outcomes to assess alignment with recommendations to improve FRQ. The NCR’s effect was analyzed through two paths—the direct effect representing institutional pressure on FRQ from the NCR introduction, and the indirect effect whereby NCR initiated FRQ changes through company characteristics. The study only found a direct significant NCR effect on FRQ in Saudi Arabia. This confirms broad institutional pressure to improve financial reporting quality in Saudi companies, enabling the achievement of a core Vision 2030 objective. The findings have implications for Saudi policymakers in evaluating reform effectiveness and identifying needs for further NCR changes. They also contribute to ongoing theoretical discussions and indicate the importance of considering country-specific institutional contexts. Overall, the study helps bridge the gap in the limited existing literature on corporate governance and FRQ in Saudi Arabia versus developed countries.